THE FLIPPED ENGLISH CLASSROOM IN EFL CONTEXT: A STUDY OF EDUCATION 4.0 - Meida Fitriana, Yumna Rasyid, Ratna Dewanti (International Journal of Advanced Science and Technology, 2020)
Indonesia education system is facing industry 4.0 era which gives many effects on the process and outcome of education. Facing education 4.0 where everything can be accessed easily and quickly, it is necessary to change the paradigm of learning as a consequence of the development of increasingly sophisticated technology. This new paradigm requires teachers who teach at the tertiary level to be able to change their basic role, not only as instructors / educators who transfer knowledge, but they are also required to use technology in teaching and make students more actively participated in learning activities. This study aimed to know the process of using Flipped Classroom in teaching English as foreign language, to know students’ perceived toward FC and to know students’ perception toward teacher’s instruction in teaching English using FC model. The data was collected by using observation, questionnaire, and interview. The findings prove that flipped Classroom model is better than traditional class in teaching English as foreign language to face education 4.0. A lot of the students seemed to have enjoyed the FL class experience. They perceived that FL as beneficial to them in terms of helping them become more responsible of their own learning, more engaged in English class activities either online or offline class, improve their English skill and more motivated to learn English more.